Cognitive control of action : selected works of David A. Rosenbaum - Rosenbaum, David A. (New York, NY : Routledge, 2024)
"In the World Library of Psychologists series, international experts present career-long collections of what they judge to be their finest pieces-extracts from books, key articles, salient research findings, and their major practical theoretical contributions. In this volume, David A. Rosenbaum reflects on his distinguished career as an eminent scholar in the field of human perception and performance. Offering a unique perspective on the cognitive psychology of physical action control, the book charts Rosenbaum's development as one of the pioneers of the field. Featuring a newly written introduction in which the author offers a unique insight into his initial work on the movement precuing technique, along with coverage of other phenomena and models related to the translation of mental life into physical behavior, the book is essential reading for students and researchers interested in human perception, motor control, and embodiment"--
Keywords: Perception; Cognition; Movement, Psychology of; Motor learning; PSYCHOLOGY / Cognitive Psychology